PELATIHAN NST. (NIJMEEGSE SCHOOLBEKWAN TEST) UNTUK DETEKSI DINI KESIAPAN ANAK MASUK SEKOLAH DASAR SEBAGAI BENTUK PROFESIONALISME GURU - Avanti Vera Risti Pramudyani; Ega Asnatasia Maharani (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2018)
The school readiness should be a part of early detection is done within the scope of the teacher in ECE. The ability of the teacher to archive the result of the test NST can be used to detect the school of readiness to enter Elementary School will provide important information for the education of the children of the next level. Early detection of the readiness of children entering the Elementary School level can be done by using the NST. (Nijmeegse Schoolbekwan Test). The activities of the Community aims to provide knowledge and insights, as well as the skills to the teacher about the school of readiness of children entering the Elementary School level in using the tool of early detection of NST. Through this training, teachers can also improve professional competence especially in doing the evaluation of the ability of the child who is ready to enter Elementary School level. Main target training is the kindergarten teacher under the auspices of the PCA Umbuharjo. Methods of implementation activities include lectures, discussion, practice, and Self and Group Reflection. Material service consists of three large materials i.e. school readiness concepts, basic concepts, and practice the use of the NST NST. The result of the activities of this devotion is in great demand this training by teachers can be seen from the number of participants and the origin of schools that exceed the target. The constraints experienced by participants of devotion when doing testing to students is community service participants (teachers) the difficulty to get the data from the entire question of tests because of limited time with learners and learners who belongs to moody.